Smart distance alert system with Blynk integration for safer gadget use - Ismail, Syila Izawana; Ismail, Nuraiza; Mohd Zaki, Aisyah Hannah; Omar, Suziana; Mohamed, Syazilawati (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Gadgets have certainly become an integral part of our daily lives. From smartphones and tablets to laptops and smartwatches, we rely on these devices to stay connected, entertained, and productive throughout the day. Excessive usage of gadgets for a long time and unhealthy habits will lead to health problems such as myopia. Using gadgets at a close distance is one of the most common unhealthy habits among gadget users, especially children. This study, called "smart distance alert system" is developed to address the unhealthy habit of using gadgets at a close distance. The developed prototype operates by measuring the distance between the user and the gadget screen using an ultrasonic sensor. The buzzer and vibration motor work as an alert system, activating when the distance is less than 50 cm. Parents or guardians will get notifications through the Blynk application. The entire prototype is controlled by NodeMicrocontroller unit.